Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary abundance, size, surface texture and their metals-carrying capacity - Xie, Qun (Ecotoxicology (London, England), 2021)
© 2021. The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.